2023
DOI: 10.5194/acp-23-4881-2023
|View full text |Cite
|
Sign up to set email alerts
|

Ice nucleation by smectites: the role of the edges

Abstract: Abstract. Smectites, like other clay minerals, have been shown to promote ice nucleation in the immersion freezing mode and likely contribute to the population of ice-nucleating particles (INPs) in the atmosphere. Smectites are layered aluminosilicates, which form platelets that depending on composition might swell or even delaminate in water by intercalation of water molecules between their layers. They comprise among others montmorillonites, hectorites, beidellites, and nontronites. In this study, we investi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 134 publications
0
0
0
Order By: Relevance
“…Quartz particles have substantially lower INP efficiencies than K-115 feldspar particles (Harrison et al, 2019), but their much higher abundance in the atmosphere can lead to an important INP contributor (Chatziparaschos et al, 2023). Nevertheless, there are other minerals present in the atmosphere, such as smectite (Kumar et al, 2023) and kaolinite (Wex et al, 2014) but their contribution to INP levels remains unknown. Some laboratory studies have found that organic-rich soil dust from agricultural lands is more INP active than inorganic desert dust (Suski et al, 2018), although 120 this fraction is typically not represented in climate models (Burrows et al 2022 pollen, and plant debris, are highly efficient ice nucleators at warm temperatures (Huang et al, 2021;Cornwell et al, 2022) and may have a substantial effect on ice crystal formation (Prenni et al, 2009).…”
Section: Introduction 45mentioning
confidence: 99%
“…Quartz particles have substantially lower INP efficiencies than K-115 feldspar particles (Harrison et al, 2019), but their much higher abundance in the atmosphere can lead to an important INP contributor (Chatziparaschos et al, 2023). Nevertheless, there are other minerals present in the atmosphere, such as smectite (Kumar et al, 2023) and kaolinite (Wex et al, 2014) but their contribution to INP levels remains unknown. Some laboratory studies have found that organic-rich soil dust from agricultural lands is more INP active than inorganic desert dust (Suski et al, 2018), although 120 this fraction is typically not represented in climate models (Burrows et al 2022 pollen, and plant debris, are highly efficient ice nucleators at warm temperatures (Huang et al, 2021;Cornwell et al, 2022) and may have a substantial effect on ice crystal formation (Prenni et al, 2009).…”
Section: Introduction 45mentioning
confidence: 99%